Simulação da qualidade da água do reservatório do Vacacaí Mirim utilizando o modelo CE-QUAL-W2 - Conterato, Taiane Menezes (2016)
The pollution and inadequate use of waters are problems that have been discussed frequently, because the water is a limited resource, which needs better management and conservation. Mathematical models of water quality have been used to assist studies relating to lakes, rivers, reservoirs and estuaries. The CE-QUAL-W2 is a software that simulates the change in water quality in the vertical and horizontal directions, it has several resources, and has been used by many authors. In Santa Maria, the Vacacaí Mirim reservoir has great importance, since it is responsible to provide part of the water that supplies the city. However, the reservoir has suffered from pollution coming from near areas. So, CE-QUAL-W2 model was used to simulate some water quality parameters of the reservoir, such as: water temperature, DO, BOD, and E.coli. We used results of monitoring realized in the years 2010 and 2011. The mean absolutes errors (MAE s) of the simulated temperatures, compared to observed, varied from 0.4 to 3.1°C, and standard errors (SE's), 0.4 to 3.5ºC. For the DO, the MAE's varied from 0.5 to1.9 mg /L and SE's, 0.7 to 2.2 mg /L. In the case of BOD, this obtained MAE's between 0.1 to 2.5 mg/L, and SE's between 0.1 to 2.5 mg/ L. Finally, the simulation of E.coli obtained MAE s between 1 and 230 MPN/100mL, and SE s between 1 to 235 MPN/100mL. Based on simulated profiles for CE-QUAL-W2, it might be said that parameters DO and temperature showed the best results, and E. coli, the biggest difficulties for calibration, due to their variability and lack of data. In the simulation scenario, firstly, it was used data by 2000 and 2010 demographic census, to estimate the population in the basin in 2050. The population increase was 56%. Although, the population at the local has increased considerably, the water quality has suffered a slight drop. Because, DO was 5.5 mg/L in 2010, and reach 4.4 mg/L in 2050, during the summer, not harming other seasons. In a second prediction, the installation of an enterprise was admitted, which launched large amount of wastewater in the reservoir, as a poultry slaughterhouse (125,000 chicken /day). In this case, the water quality showed a sharper declined, which increase in organic matter, reaching 5.1 mg/L at some points, and decreased of DO, with concentrations close to zero, not obeying the limits established by CONAMA Resolution 357/05, for the urban supply. In this way, we can said that the model simulates the behavior of water quality parameters in Vacacai Mirim reservoir, and makes predictions, it may be useful in other studies at the local and in reservoir management.